The archaeology of 'underdog sites' in the Douro Valley : from prehistory to the modern age - Sánchez de la Parra-Pérez, Santiago,; Díaz-Navarro, Sonia,; Fernández-Lozano, Javier,; Jiménez Gadea, Javier, (Access archaeology., 2021)
This volume brings together the best presentations from the 8th and 9th Archaeology of the Douro Valley meetings, held in Avila (2018) and Astorga (2019). Papers aim to show the importance of projects that have been left in the background despite obtaining interesting archaeological data about the occupation of this valley and its evolution.